PEMAHAMAN KONSEPTUAL DAN KELANCARAN PROSEDURAL SISWA DALAM MATERI BENTUK AKAR DI KELAS X SMA - Nola Anggita; Yulis Jamiah; Dian Ahmad BS (Universitas Tanjungpura, 2018)
Abstract This research was conducted to find out conceptual understanding and procedural fluency of students on root form material in SMA Muhammadiyah 2 Pontianak. This research used descriptive method with quantitative approach. Subjects in this research were students of class X MIA with a total of 27 students. Written tests are used to collect data. Based on the analysis of research data obtained conceptual understanding of each indicator are: (1) indicator 1 is in very low category (4%); (2) indicator 2 is in very low category (34%); (3) indicator 3 included in high category (80%); (4) indicator 4 is in very low category (28%) and (5) indicator 5 is in low category (55%). The procedural fluency of students in every aspect are: (1) flexible aspects are in very low category (28%); (2) efficient aspects are in very low category (28%) and (3) accurate aspects are in very low category (37%). Conceptual understanding and procedural fluency of students are in very low category with a percentage of 40% and 31% respectively. Keywords: Conceptual Understanding, Procedural Fluency